2019
DOI: 10.3390/brainsci9100266
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Plasminogen Activator and MRI Signs of Cerebral Small Vessel Disease

Abstract: Cerebral small vessel disease (SVD) is one of the leading causes of cognitive impairment and stroke. The importance of endothelial dysfunction and high blood–brain barrier (BBB) permeability in pathogenesis, together with ischemia, is under discussion. The aim of this study was to clarify the relationship between tissue plasminogen activator (t-PA), plasminogen activator inhibitor (PAI-1), and magnetic resonance imaging (MRI) signs of SVD. We examined 71 patients (23 men and 48 women; mean age: 60.5 ± 6.9 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 35 publications
0
3
0
2
Order By: Relevance
“…. Contrary, another recent study from Moscow found that t-PA levels were associated with WMHs and EPVSs, while PAI-1 levels were not associated with cerebral SVD(Dobrynina et al, 2019). However, all patients in the Maastricht stroke study had a lacunar stroke, but only half of the patients in the Moscow study had a lacunar stroke.…”
mentioning
confidence: 60%
“…. Contrary, another recent study from Moscow found that t-PA levels were associated with WMHs and EPVSs, while PAI-1 levels were not associated with cerebral SVD(Dobrynina et al, 2019). However, all patients in the Maastricht stroke study had a lacunar stroke, but only half of the patients in the Moscow study had a lacunar stroke.…”
mentioning
confidence: 60%
“…T-PA, along with its well-known role in fibrinolysis, has pleiotropic activities in the central nervous system-neuroplasticity, excitotoxicity, and influence on BBB permeability [57]. Previously, we established a relationship between increased t-PA levels and MRI changes associated with high BBB permeability [58]. However, there are reasons to believe that the combined effect of t-PA, NO, and its oxidation products provides a continuum of vascular and cerebral damage associated with neurodegeneration and mixed vascular-degenerative forms of the CSVD.…”
Section: Discussionmentioning
confidence: 99%
“…При МРТ-исследовании на магнитно-резонансном томографе с величиной магнитной индукции 3 Тл («Siemens Healthineers AG») оценивали МРТ-признаки ЦМА [2] и МРТ-признаки БА [4,5], исключали наличие иных МРТ-изменений. Кли-прогрессирования ЦМА [13,14], можно предполагать, что биохимические маркеры астроцитарной реакции будут наиболее подходящими кандидатами для диагностики ЦМА, ассоциированной с нейродегенерацией. Основным признанным маркером активации астроглии является глиофибриллярный кислый белок (GFAP).…”
Section: Biochemical Markers Of Neurodegeneration In Patients With Ce...unclassified
“…В ранее проведённых исследованиях заболеваний с КР повышение GFAP в крови и ЦСЖ рассматривалось как маркер БА и ассоциировалось с патологическим астроглиозом[19][20][21][22][23][24][25][26][27]. Результаты нашего исследования свидетельствуют о GFAP как маркере ЦМА, что, учитывая определяющее значение в развитии заболевания высокой проницаемости ГЭБ[14], может объясняться реактивностью астроцитов в поддержании гомеостаза ГЭБ. О значении данного маркера для ЦМА и развития смешанных форм свидетельствуют результаты его исследования при БА[27].…”
unclassified